Drawbacks of Blast Vibration Regulations - Mark Svinkin (International Society of Explosives Engineers, 2003)
The purpose of this paper is to present an overview of recommended existing criteria of ground vibrations generated by blasting. It is shown that these criteria have limited liability because they were found for specific categories of structures. A new approach based on measurement of structure vibrations is suggested for assessment of damage in structures subjected to blasting vibrations. This approach provides the flexibility of implicitly considering a variety of soil-structure interaction and structure conditions. It is explained a new frequency-independent safe-level criterion of 51 mm/s (2 in/s) for the PPV of structural vibrations. Attention is brought to use seismographs properly calibrated for the required frequency range. Positive flexibility is demonstrated in assessment of structure and component of concern vibrations from blasting.